Green shadows: exploring tropes of ecophobia in jean rhys’ wide sargasso sea - Jana, Pooja; Padmaja, C.V. (Penerbit Universiti Kebangsaan Malaysia, 2024)
E. O. Wilson commented that phobia is not innately present but acquired. The article highlights how the fear of nature shapes the cultural and social behaviours of Man. Wide Sargasso Sea, written by Jean Rhys, primarily portrayed as a postcolonial response to Charlotte Bronte’s Jane Eyre, is replete with gothic imagery. Fear and anxiety of nature are commonly found as the centre of Gothicised texts throughout literary history, wreathing concerns of ecophobia, a term used by Simon Estok to define this irrational traumatic response to the natural. The article aims to explore tropes of ecophobia, fear of nature, through the two main protagonists of the novel- Rochester and Antoinette. The EcoGothic reverberations in the text highlight intersections between the biophilic human psyche and the contrasting colonial upbringing that develop into an aversion towards Nature and its subjects. The article draws from concepts of colonialism and Gothic shifting focus towards EcoGothic, ensuing the ecological destruction. Further, it discusses tropes of ecophobia which is also a trajectory of the related aversion to otherness. Ecophobic tendencies tune themselves into destruction, manipulation and domination, hastening climate degradation. The world in contemporary times suffers from anxiety related to the altering changes in the environment, and the article attempts to briefly decode the reasons for this disconnect while also putting the theories of ecophobia at the forefront in attempt to re-analyse postcolonial texts.